Domestic Investment and Economic Growth Nexus: Does Absorptive Capacity Matter in the African Countries? - Ogunyomi-Oluyomi, Oluwatosin Olatunji; George , Emmanuel Oladapo; Maku, Olukayode Emmanuel; Adelowokan , Oluwaseyi A. (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2023)
This study empirically examined the role of the country’s absorptive capacity on the impact of domestic investment on economic growth in the selected five African countries over the study period of 1970 to 2019. In specific, the study examined the impact of domestic investment on economic growth from two models, without the country’s absorptive capacity and with the country’s absorptive capacity. Further, a robust linear ordinary least squares (OLS) methodology including static panel OLS and panel cointegration estimators was employed. The study found that only changes in financial development and infrastructures positively cause changes in the domestic investment-economic growth nexus in the short run while in the long run, trade openness enhances the positive impact of domestic investment on economic growth in African countries. In addition, the study found that domestic investment retards economic growth without the country’s absorptive capacity in the short run and long run respectively in African countries. Therefore, the study recommended that policymakers should invest heavily in infrastructure and financial development systems as well as encourages trade openness for a stable domestic investment-economic growth nexus in African countries.